Forensic intelligence applied to questioned document analysis: A model and its application against organized crime. Issue 4 (July 2017) - De Alcaraz-Fossoul, Josep; Roberts, Katherine A.
Abstract: The capability of forensic sciences to fight crime, especially against organized criminal groups, becomes relevant in the recent economic downturn and the war on terrorism. In view of these societal challenges, the methods of combating crime should experience critical changes in order to improve the effectiveness and efficiency of the current resources available. It is obvious that authorities have serious difficulties combating criminal groups of transnational nature. These are characterized as well structured organizations with international connections, abundant financial resources and comprised of members with significant and diverse expertise. One common practice among organized criminal groups is the use of forged documents that allow for the commission of illegal cross-border activities. Law enforcement can target these movements to identify counterfeits and establish links between these groups. Information on document falsification can become relevant to generate forensic intelligence and to design new strategies against criminal activities of this nature and magnitude. This article discusses a methodology for improving the development of forensic intelligence in the discipline of questioned document analysis. More specifically, it focuses on document forgeries and falsification types used by criminal groups. It also describes the structure of international criminal organizations that use document counterfeits as means to conduct unlawful activities. The model presented is partially based on practical applications of the system that have resulted in satisfactory outcomes in our laboratory. Highlights: Criminals use forged documents to commit illegal cross-border activities. Law enforcement can target international activities to identify and relate criminal groups. Questioned document analysis can be used to link criminal groups by creating forensic intelligence. A methodology is presented to help develop forensic intelligence based on counterfeit documents.